2022
DOI: 10.1038/s41598-022-17749-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender dysphoria in twins: a register-based population study

Abstract: Both genetic and environmental influences have been proposed to contribute to the variance of gender identity and development of gender dysphoria (GD), but the magnitude of the effect of each component remains unclear. We aimed to examine the prevalence of GD among twins and non-twin siblings of individuals with GD, using data derived from a large register-based population in Sweden over the period 2001–2016. Register data was collected from the Statistics Sweden and the National Board of Health and Welfare. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, evidence from multiple neuroimaging studies has not given support to this, and alternative hypotheses have been proposed 9 10. Genetic factors have also been observed to play a role in GD, and twin studies have been mostly employed to enlighten the development in GD 11–13. Even though the existing evidence remains largely inconclusive, genetic factors seem to be involved through altered sex hormone signalling; the oestrogen and androgen receptors seem to be implicated in the genetic basis of GD 14.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence from multiple neuroimaging studies has not given support to this, and alternative hypotheses have been proposed 9 10. Genetic factors have also been observed to play a role in GD, and twin studies have been mostly employed to enlighten the development in GD 11–13. Even though the existing evidence remains largely inconclusive, genetic factors seem to be involved through altered sex hormone signalling; the oestrogen and androgen receptors seem to be implicated in the genetic basis of GD 14.…”
Section: Introductionmentioning
confidence: 99%
“…They found that 39.1% of monozygotic twins were concordant for gender dysphoria, which seemingly is a larger percent than in an unrelated population. Significantly, Karamanis et al [14], in a recent study from a large Swedish registry of siblings of gender dysphoria individuals, some of whom were twins, found that the proportion of different-sex twins both presenting with gender dysphoria (37%) was higher than that in same-sex twins and in non-twin sibling pairs (0.16%), suggesting that a shared environment during the intrauterine period is what may lead to gender dysphoria rather than genes themselves. However, no study of the heritability of gender dysphoria comparing concordance among monozygotic to dizygotic twins has yet been performed.…”
mentioning
confidence: 99%